Information content of inter-transaction time: A structural approach - Ryu, Doojin (Journal of Business Economics and Management, 2015)
This study examines the information role of inter-transaction time by employing a structural market microstructure model. By analyzing the intraday data of the KOSPI200 futures market, we find that the inter-transaction time (i.e., time between two consecu- tive trades) reveals significant information, and that fast trading is indicative of informed trading. This result remains robust when the effect of trade size is incorporated into the model. Our regression analysis indicates that the information role of inter-transaction time becomes more important when informed trading is less concentrated, liquidity is lower, and the market is more volatile.